ナンキョク ショウワキチ ニ オケル タイキチュウ チッソ サンカブツ NO X ノ レンゾク ソクテイ - 安孫子, 勤; アビコ, ツトム; 鳥居, 鉄也; トリイ, テツヤ; ABIKO, Tsutomu; TORII, Tetsuya (国立極地研究所, 1977)
P(論文) 地球大気の汚染をモニタリングするために,第16次南極観測隊によって,1975年の越冬期間中,昭和基地において大気中の窒素酸化物(NO_x)の連続測定が行われた.その結果,7月初旬から9月中旬にかけて,ブリザード襲来に伴う大気中の窒素酸化物濃度の変化が観測されたが,これは低気圧によって低緯度地方から運ばれてくる空気によるものと思われる. For the purpose of monitoring the global atmospheric air pollution on the earth, the atmospheric nitrogen oxides at Syowa Station in East Antarctica were continuously measured by the 16th Japanese Antarctic Research Expedition (JARE) during the wintering period in 1975. In the period of early July to mid September the regular variation of the atmospheric NO_x concentration was clearly observed whenever a blizzard hits Lutzow-Holm Bay. This variation would indicate the possible existence of NO_x compounds that have been transported from the lower latitudes by a cyclone. departmental bulletin paper